Voluntary medical adult male circumcision for HIV prevention in South Africa: The tensions between medicalised modernity and traditional practices - Howard-Payne, Lynlee (PINS-Psychology in Society, 2016)
While a staggered rollout of voluntary medical adult male circumcision (VMAMC) for HIV prevention has been initiated, traditional male circumcision (TMC) and non-circumcision are important signifiers of cultural identity and masculinity in South Africa. As part of a larger study, repeat semi-structured interviews with 30 adult men from Alexandra Township were conducted. A Straussian grounded theory approach was utilised to identify and unpack the theoretical categories that underpin the tension between tradition, modernity, and medicine within the context of VMAMC and HIV prevention. This tension is made possible by a necessity to maintain and uphold traditional practices that denote the cultural meanings of masculinity and adulthood with TMC or non-circumcision, while also considering the state-promoted uptake of novel prevention efforts given the ongoing concern of HIV prevalence in South Africa. The ways in which this tension is negotiated has bearing on public responses to VMAMC for HIV prevention and the uptake thereof. This study highlights the complexity of seemingly “simple” solutions to HIV prevention interventions through once-off body directed strategies to underscore the importance of critical public health psychology to the advancement and implementation of such interventions in South Africa.